Emergy and the rules of emergy accounting applied to calculate transformities for some of the primary, secondary, and tertiary exergy flows of the Geobiosphere - Campbell, Daniel Elliott; Lu, Hongfang (Frontiers in Energy Research, 2024)
Emergy is a concept that is important for understanding problems in accounting for the health and integrity of ecological and social systems. Success in the evolutionary competition among systems depends on maximizing the emergy captured by a system that is then fed back to bring in more exergy. For this reason, "emergy" in the form of maximum empower (i.e., maximum emergy flow measured in solar emjoules or sej/unit time) provides a unified, thermodynamically controlled decision criterion by which the behavior of all systems is constrained. The fact that maximum empower and not maximum profit is nature's decision criterion makes it critical that more people become familiar with emergy evaluations and how to use the results of these analyses in decision-making. A new approach to emergy evaluation is proposed that focuses on developing more accurate assessments of the spatial and temporal emergy accounting required for the creation of products and services. These emergy evaluations include the accumulated past action of exergy in creating key system components including vegetation biomass and the accumulated knowledge of workers in the economy, which will result in emergy assessments that better reflect the capacity of the products and services to do work in their systems. An analysis of the Geobiosphere is presented as a "white box" model of the secondary and tertiary flows of wind and water in the global system. Key factors identified are the separation of the wind into two components, a factor controlling vertical diffusion with transformity, 715 sej J-1 and a second transformity governing surface friction of 1215 sej J-1 . Also, water systems are fully defined with transformities of 302,900 to 1,440,000 sej J-1 for geostrophic flows. Past emergy analyses show that managers should develop policies that will maximize the empower flowing through their systems. The problem of maximizing the empower captured occurs within the context of a set of forcing functions impinging on a system from the next larger system, and since these forcing functions are always changing, maximum power should not be thought of as a fixed endpoint, but rather as a constant state of seeking this goal.